plz solve this guy's
Attachments:
![](https://hi-static.z-dn.net/files/d38/7c8336e0dc3328ef377c00518295ce45.jpg)
Answers
Answered by
3
Hey There!!
Here we have:
![x=3+\sqrt{8} \\ \\ \\ \implies \frac{1}{x} = \frac{1}{3+\sqrt{8}} \\ \\ \\ \implies \frac{1}{x} = \frac{1}{3+\sqrt{8}} \times \frac{3-\sqrt{8}}{3-\sqrt{8}} \\ \\ \\ \implies \frac{1}{x} = \frac{3-\sqrt{8}}{9-8} \\ \\ \\ \implies \frac{1}{x} = 3-\sqrt{8} x=3+\sqrt{8} \\ \\ \\ \implies \frac{1}{x} = \frac{1}{3+\sqrt{8}} \\ \\ \\ \implies \frac{1}{x} = \frac{1}{3+\sqrt{8}} \times \frac{3-\sqrt{8}}{3-\sqrt{8}} \\ \\ \\ \implies \frac{1}{x} = \frac{3-\sqrt{8}}{9-8} \\ \\ \\ \implies \frac{1}{x} = 3-\sqrt{8}](https://tex.z-dn.net/?f=x%3D3%2B%5Csqrt%7B8%7D+%5C%5C+%5C%5C+%5C%5C+%5Cimplies+%5Cfrac%7B1%7D%7Bx%7D+%3D+%5Cfrac%7B1%7D%7B3%2B%5Csqrt%7B8%7D%7D+%5C%5C+%5C%5C+%5C%5C+%5Cimplies+%5Cfrac%7B1%7D%7Bx%7D+%3D+%5Cfrac%7B1%7D%7B3%2B%5Csqrt%7B8%7D%7D+%5Ctimes+%5Cfrac%7B3-%5Csqrt%7B8%7D%7D%7B3-%5Csqrt%7B8%7D%7D+%5C%5C+%5C%5C+%5C%5C+%5Cimplies+%5Cfrac%7B1%7D%7Bx%7D+%3D+%5Cfrac%7B3-%5Csqrt%7B8%7D%7D%7B9-8%7D+%5C%5C+%5C%5C+%5C%5C+%5Cimplies+%5Cfrac%7B1%7D%7Bx%7D+%3D+3-%5Csqrt%7B8%7D)
![\implies x+\frac{1}{x} = (3+\sqrt{8}) + (3-\sqrt{8}) \\ \\ \\ \implies x+\frac{1}{x} = 6 \implies x+\frac{1}{x} = (3+\sqrt{8}) + (3-\sqrt{8}) \\ \\ \\ \implies x+\frac{1}{x} = 6](https://tex.z-dn.net/?f=%5Cimplies+x%2B%5Cfrac%7B1%7D%7Bx%7D+%3D+%283%2B%5Csqrt%7B8%7D%29+%2B+%283-%5Csqrt%7B8%7D%29+%5C%5C+%5C%5C+%5C%5C+%5Cimplies+x%2B%5Cfrac%7B1%7D%7Bx%7D+%3D+6+)
Now,
![x^2+\frac{1}{x^2} \\ \\ \\ = x^2 + \frac{1}{x^2} +2 - 2 \\ \\ \\ = x^2 + 2(x) \left(\frac{1}{x} \right) + \frac{1}{x^2} - 2 \\ \\ \\ = \left(x+\frac{1}{x} \right)^2 - 2 \\ \\ \\ = 6^2 - 2 \\ \\ \\ = 36 - 2 \\ \\ \\ = 34 \\ \\ \\ \\ \\ \implies \boxed{x^2+\frac{1}{x^2}=34} x^2+\frac{1}{x^2} \\ \\ \\ = x^2 + \frac{1}{x^2} +2 - 2 \\ \\ \\ = x^2 + 2(x) \left(\frac{1}{x} \right) + \frac{1}{x^2} - 2 \\ \\ \\ = \left(x+\frac{1}{x} \right)^2 - 2 \\ \\ \\ = 6^2 - 2 \\ \\ \\ = 36 - 2 \\ \\ \\ = 34 \\ \\ \\ \\ \\ \implies \boxed{x^2+\frac{1}{x^2}=34}](https://tex.z-dn.net/?f=x%5E2%2B%5Cfrac%7B1%7D%7Bx%5E2%7D+%5C%5C+%5C%5C+%5C%5C+%3D+x%5E2+%2B+%5Cfrac%7B1%7D%7Bx%5E2%7D+%2B2+-+2+%5C%5C+%5C%5C+%5C%5C+%3D+x%5E2+%2B+2%28x%29+%5Cleft%28%5Cfrac%7B1%7D%7Bx%7D+%5Cright%29+%2B+%5Cfrac%7B1%7D%7Bx%5E2%7D+-+2+%5C%5C+%5C%5C+%5C%5C+%3D+%5Cleft%28x%2B%5Cfrac%7B1%7D%7Bx%7D+%5Cright%29%5E2+-+2+%5C%5C+%5C%5C+%5C%5C+%3D+6%5E2+-+2+%5C%5C+%5C%5C+%5C%5C+%3D+36+-+2+%5C%5C+%5C%5C+%5C%5C+%3D+34+%5C%5C+%5C%5C+%5C%5C+%5C%5C+%5C%5C+%5Cimplies+%5Cboxed%7Bx%5E2%2B%5Cfrac%7B1%7D%7Bx%5E2%7D%3D34%7D)
Hope it helps
Purva
Brainly Community
Here we have:
Now,
Hope it helps
Purva
Brainly Community
abhi569:
You forget to right x, [ after 2 lines from NOW]
Answered by
2
x = 3 + √8
![\frac{1}{x} = \frac{1}{3 + \sqrt{8} } \frac{1}{x} = \frac{1}{3 + \sqrt{8} }](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7Bx%7D++%3D++%5Cfrac%7B1%7D%7B3+%2B++%5Csqrt%7B8%7D+%7D+)
By Rationalization,
![\frac{1}{x} = \frac{1}{3 + \sqrt{8} } \times \frac{3 - \sqrt{8} }{ 3 - \sqrt{8} } \\ \\ \\ \frac{1}{x} = \frac{3 - \sqrt{8} }{(3 + \sqrt{8} )(3 - \sqrt{8} )} \frac{1}{x} = \frac{1}{3 + \sqrt{8} } \times \frac{3 - \sqrt{8} }{ 3 - \sqrt{8} } \\ \\ \\ \frac{1}{x} = \frac{3 - \sqrt{8} }{(3 + \sqrt{8} )(3 - \sqrt{8} )}](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7Bx%7D++%3D++%5Cfrac%7B1%7D%7B3+%2B++%5Csqrt%7B8%7D+%7D++%5Ctimes++%5Cfrac%7B3+-++%5Csqrt%7B8%7D+%7D%7B++3+-++%5Csqrt%7B8%7D+%7D++%5C%5C++%5C%5C++%5C%5C++%5Cfrac%7B1%7D%7Bx%7D++%3D++%5Cfrac%7B3+-++%5Csqrt%7B8%7D+%7D%7B%283+%2B++%5Csqrt%7B8%7D+%29%283+-++%5Csqrt%7B8%7D+%29%7D+)
××××××××××××××
We know,
(a + b)(a - b) = a² - b²
××××××××××××××××
Applying formula on denominator,
![\frac{1}{x} = \frac{ 3 - \sqrt{8} }{ {3}^{2} - {( \sqrt{8}) }^{2} } \\ \\ \\ \frac{1}{x} = \frac{3 - \sqrt{8} }{9 - 8} \\ \\ \\ \frac{1}{x} = \frac{3 - \sqrt{8} }{1} \\ \\ \\ \frac{1}{x} = 3 - \sqrt{8} \frac{1}{x} = \frac{ 3 - \sqrt{8} }{ {3}^{2} - {( \sqrt{8}) }^{2} } \\ \\ \\ \frac{1}{x} = \frac{3 - \sqrt{8} }{9 - 8} \\ \\ \\ \frac{1}{x} = \frac{3 - \sqrt{8} }{1} \\ \\ \\ \frac{1}{x} = 3 - \sqrt{8}](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7Bx%7D++%3D++%5Cfrac%7B+3+-++%5Csqrt%7B8%7D+%7D%7B+%7B3%7D%5E%7B2%7D+-++%7B%28+%5Csqrt%7B8%7D%29+%7D%5E%7B2%7D++%7D++%5C%5C++%5C%5C++%5C%5C++%5Cfrac%7B1%7D%7Bx%7D++%3D++%5Cfrac%7B3+-++%5Csqrt%7B8%7D+%7D%7B9+-+8%7D++%5C%5C++%5C%5C+%5C%5C+++%5Cfrac%7B1%7D%7Bx%7D++%3D++%5Cfrac%7B3+-++%5Csqrt%7B8%7D+%7D%7B1%7D++%5C%5C++%5C%5C++%5C%5C++%5Cfrac%7B1%7D%7Bx%7D++%3D+3+-++%5Csqrt%7B8%7D+)
Now,
![{x}^{2} + \frac{1}{ {x}^{2} } \\ \\ \\ => (3 + \sqrt{8} )^{2} + {(3 - \sqrt{8}) }^{2} \\ \\ \\ {x}^{2} + \frac{1}{ {x}^{2} } \\ \\ \\ => (3 + \sqrt{8} )^{2} + {(3 - \sqrt{8}) }^{2} \\ \\ \\](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B2%7D++%2B+++%5Cfrac%7B1%7D%7B+%7Bx%7D%5E%7B2%7D+%7D++%5C%5C++%5C%5C++%5C%5C++%3D%26gt%3B+%283+%2B++%5Csqrt%7B8%7D+%29%5E%7B2%7D++%2B++%7B%283+-++%5Csqrt%7B8%7D%29+%7D%5E%7B2%7D++%5C%5C++%5C%5C++%5C%5C)
×××××××××××××××××
We know,
(a + b)² = a² + b² + 2ab
(a - b)² = a² + b² - 2ab
××××××××××××××××××××
Applying formula,
=> (3 + √8)² + (3 - √8)²
=> (3)² + (√8)² + 6√8 + (3)² - (√8)² - 6√8
=> 9 + 8 + 6√8 + 9 + 8 - 6√8
=> 9 + 8 + 9 + 8
=> 17 + 17
=> 34
I hope this will help you
(-:
By Rationalization,
××××××××××××××
We know,
(a + b)(a - b) = a² - b²
××××××××××××××××
Applying formula on denominator,
Now,
×××××××××××××××××
We know,
(a + b)² = a² + b² + 2ab
(a - b)² = a² + b² - 2ab
××××××××××××××××××××
Applying formula,
=> (3 + √8)² + (3 - √8)²
=> (3)² + (√8)² + 6√8 + (3)² - (√8)² - 6√8
=> 9 + 8 + 6√8 + 9 + 8 - 6√8
=> 9 + 8 + 9 + 8
=> 17 + 17
=> 34
I hope this will help you
(-:
Similar questions